2007
DOI: 10.1051/0004-6361:20077517
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chemi-ionization and chemi-recombination processes on hydrogen line shapes in M dwarfs

Abstract: Aims. We study the influence of chemi-ionization in H * (n) + H(1s) collisions and inverse chemi-recombination processes on the population of higher levels and consequently on profiles of hydrogen lines in the atmospheres of late type (M) stars. Methods. Modeling, using general stellar atmosphere code PHOENIX to reveal the importance of the inclusion of such processes. Results. We demonstrate for the first time observationally detectable effects of these chemi-processes on stellar spectra. Conclusions. It is v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(72 citation statements)
references
References 12 publications
1
71
0
Order By: Relevance
“…Another important thing is that the presented results suggest that these processes, due to their influence on free electron density and excited state populations in the atmospheres of M red dwarfs, should also influence the atomic spectral line shapes (see e.g. Mihajlov et al (2007b)). …”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Another important thing is that the presented results suggest that these processes, due to their influence on free electron density and excited state populations in the atmospheres of M red dwarfs, should also influence the atomic spectral line shapes (see e.g. Mihajlov et al (2007b)). …”
Section: Introductionmentioning
confidence: 77%
“…In previous works (Mihajlov et al 2003(Mihajlov et al , 2007b related to the photosphere of a M red dwarf with temperature near to 4000 K, it has been shown that on populations of hydrogenic Rydberg states in this photosphere as well as on its other characteristics, influence strongly just the chemi-ionization processes (1a) and (1b) with 4 ≤ n ≤ 8. It is clear that, already because of this, it is indispensable to take into account the changes of rate coefficients of these processes, which, in accordance with our results, are particularly large for n ≤ 6.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the examined processes, due to their influence on the excited state populations and the free electron density, should also influence the atomic spectral line shapes. Figure 5 (from [23]) shows the line profiles of H α , H δ , H Pa with and without the inclusion of (1a) and (1b) processes. Profiles are synthesized with PHOENIX code [8] with Stark broadening contribution.…”
Section: Astrophysical Targetsmentioning
confidence: 99%
“…It was demonstrated that the absorption processes (1) in the optical part of spectra should be considered in the Solar photosphere and the lower chromosphere together, since in this case their influences on the opacity are similar. In subsequent papers (Mihajlov et al 1993(Mihajlov et al , 1994a, the absorption processes (1) were investigated in more detail and their contributions to the solar opacity were determined by using standard Solar atmosphere models (Vernazza et al 1981;Maltby et al 1986). Then, these contributions were compared with the contributions of other relevant radiative processes, namely…”
Section: Introductionmentioning
confidence: 99%
“…In Mihajlov et al (1993Mihajlov et al ( , 1994a) the part of the optical region 365 nm ≤ λ ≤ 820 nm was taken into account. It was found that in this region the processes (1) give a contribution of 10-12% in comparison with processes (2).…”
Section: Introductionmentioning
confidence: 99%